Infiltrative cardiomyopathies. Contribution of echocardiography (2019)
Infiltrative cardiomyopathies are characterised by the deposit of abnormal substances within the ventricular wall that cause stiffness and thus progressive diastolic dysfunction, which typically precedes systolic dysfunction. These conditions can be classified into two large groups, depending on their phenotype: those that simulate ischaemic heart disease or dilated cardiomyopathy, and those that simulate hypertrophic or hypertensive cardiomyopathy. The first group includes, sarcoidosis, haemochromatosis, and Wegener's granulomatosis, while the second group includes, amyloidosis, Anderson-Fabry disease, Danon disease, Friedreich's ataxia, myocardial oxalosis, and mucopolysaccharidosis. In this chapter, a description will be made of the most relevant aspects of the echocardiography approach into the most common infiltrative cardiomyopathies, highlighting the most notable findings that should make one suspect each one these diseases, and to establish the need to widen the study with other diagnostic methods. © 2019 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular